Educator's sense of efficacy in the context of teaching in Malaysian private higher education institutions - Low, Chan Mee; Elias, Habibah (The Journal of International Social Research, 2010)
This study focused on the educator’s sense of efficacy in three Malaysian private higher institutions. This study examined whether there is any difference in the educator’s sense of efficacy in teaching international and Malaysian students. It also investigates the teacher sense of efficacy in relation to age, years of teaching experience and level of education. The study was conducted by using the teacher sense of efficacy scale by Tschannen-Moran and Woolfolk Hoy (2001). The sample consisted of 59 lecturers from Faculty of Modern Languages and Communication. The results showed that there are significant positive correlations in teacher’s sense of efficacy in relation to age (r=.277, p < 0.05), years of teaching experience (r=.287, p<0.05) and level of education (rs=.284, p>0.05). There are significant differences in teaching Malaysian students and International students in relation to efficacy for instructional strategies (t=-2.963, p<0.05), efficacy for classroom management (t=2.531,p<0.05) and efficacy for student engagement (t= -2.825, <0.05). The implication of the teachers’ sense of efficacy was discussed.